The Role Of Digital Wallet Transactions In Corporate Cash Flow Reporting - Francisca Olivine Wardiyanti; Dian Saripujiana; Indah Zakiyah; Verawaty Verawaty (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the role of digital wallet transactions in corporate cash flow reporting using a literature review approach. The rapid development of financial technology (fintech) has transformed transaction mechanisms, with digital wallets emerging as a dominant payment method in modern business practices. However, this transformation presents challenges to traditional accounting frameworks, particularly in the recognition, classification, and reporting of cash flows. This research employs a qualitative method through a systematic literature review of relevant academic journals, professional reports, and accounting standards. The data are analyzed using content analysis techniques to identify key themes, including the characteristics of digital wallet transactions, classification issues, impacts on financial transparency, auditing challenges, and regulatory gaps. The findings indicate that digital wallet transactions differ significantly from conventional cash transactions due to their real-time processing, involvement of third-party intermediaries, and platform-based fund management. These characteristics create ambiguity in determining whether such transactions should be classified as cash, cash equivalents, or other financial assets. Additionally, while digital wallets enhance real-time financial monitoring and decision-making, they also introduce complexities in accounting systems, internal controls, and auditing processes. The study concludes that the increasing adoption of digital wallets necessitates the adaptation of accounting standards and practices. Clear and consistent regulatory guidance is required to ensure the transparency, reliability, and comparability of cash flow reporting. This research contributes to the literature by bridging the gap between fintech developments and financial reporting practices, offering insights for academics, practitioners, and regulators in addressing the challenges of digital financial transactions.